2020
DOI: 10.1111/jvh.13276
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of HCC in chronic hepatitis C patients with advanced hepatic fibrosis who achieved SVR following DAAs: A prospective study

Abstract: Liver cirrhosis is an important risk factor for hepatocellular carcinoma. The reported annual incidence of HCC is about 3%‐8% in CHC cirrhotic patients. Based on the Cochrane systematic review, there was no clear evidence, on the long‐term clinical effects of DAAs in patients achieving SVR, as regard liver cirrhosis‐related HCC incidence. The aim of the study was to determine the incidence of HCC in chronic hepatitis C patients genotype IV with liver cirrhosis and advanced liver fibrosis after achieving SVR fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 32 publications
4
46
0
Order By: Relevance
“…As the negative predictive value for the cut-off of 17.5 kPa was very high at 99.7%, this could suggest that within the first three years after cure for hepatitis C, monoinfected patients with no prior episode of HCC or decompensated cirrhosis and with a pretreatment LSM below 17.5 kPa may not benefit from HCC surveillance. However, patients Our findings are in line with recent study by Shiha et al [31] that followed 2372 patients monoinfected with HCV with no prior episodes of decompensated cirrhosis or HCC who achieved SVR after treatment with DAA for an average of 23.6 months. In 638 patients with a pretreatment LSM of 10.3-16.3 kPa Shiba et al found a HCC incidence rate of 0.664/100 PY compared to 2.917/100 PY among 1734 patients with a pretreatment LSM of �16.4 kPa.…”
Section: Discussionsupporting
confidence: 92%
“…As the negative predictive value for the cut-off of 17.5 kPa was very high at 99.7%, this could suggest that within the first three years after cure for hepatitis C, monoinfected patients with no prior episode of HCC or decompensated cirrhosis and with a pretreatment LSM below 17.5 kPa may not benefit from HCC surveillance. However, patients Our findings are in line with recent study by Shiha et al [31] that followed 2372 patients monoinfected with HCV with no prior episodes of decompensated cirrhosis or HCC who achieved SVR after treatment with DAA for an average of 23.6 months. In 638 patients with a pretreatment LSM of 10.3-16.3 kPa Shiba et al found a HCC incidence rate of 0.664/100 PY compared to 2.917/100 PY among 1734 patients with a pretreatment LSM of �16.4 kPa.…”
Section: Discussionsupporting
confidence: 92%
“…The study included 4400 consecutive patients, with liver cirrhosis and advanced fibrosis who achieved a sustained virologic response (SVR). The derivation cohort included 2372 patients (638 patients with F3 and 1734 with F4 stage) and their characteristics are described previously 14 . The patients were followed for an average of 23.60 ± 8.25 months after the cessation of DAA treatment and during this period, 109 patients developed HCC, with an annual incidence of 2.338/100 per year (95% CI = 1.942‐2.814).…”
Section: Resultsmentioning
confidence: 99%
“…SVR was associated with a 73% reduction in the overall relative risk for HCC recurrence. An Egyptian cohort of 2372 patients infected by genotype 4 HCV with advanced liver fibrosis and cirrhosis was prospectively followed for at least 12 months [ 38 ]. The overall HCC incidence was 2.3 per 100 patient-years.…”
Section: Occurrence Of Hcc After Treatment With Daasmentioning
confidence: 99%